Body experience and mirror behaviour in female eating disorders patients and non clinical subjects - Probst, Michel; Pieters, Guido; Vancampfort, Davy; Vanderlinden, Johan (2008)
Summary: Recently the attention for mirror exercises in therapies targeted specifically to body experience concerns has increased. This retrospective study will explore the mirror behaviour of anorexia nervosa (AN), bulimia nervosa (BN) and non-clinical female subjects (CG) and investigate whether mirror avoidance or checking are related to negative body experiences. The group of eating disorders consisted of 560 AN and 314 BN patients. The control group consisted of 1151 female subjects. The Body Attitude Test and the Eating Disorder Inventory subscales drive for thinness and body dissatisfaction were used. To explore the mirror behaviour, one item of the Body Attitude Test'I am observing my appearance in the mirror' was used. Summary: Nonparametric analyses (Spearman rho correlations, Kruskal-Wallis and Mann Whitney test) were used because of the categorical data. BN patients observed their body more often in the mirror than AN patients and the control subjects do. Age and BMI showed no significant main effect of mirror frequency. The relation between the frequency of mirror behaviour and body experience were significant but low (under .40). AN patients and control subjects with a mirror checking behaviour had a more negative body experience than those with mirror avoidance behaviour. In the BN group, no differences were found. There is support to integrate mirror exercises in a treatment of eating disorder patients. From a clinical point, mirror exercises are preferably combined with a body oriented therapy within a multidimensional cognitive behavioural approach. Recommendations for mirror exercises based on the clinical experience are given
Tema broja: Eating disorders and obesity
Bibliografija: str. 346-348
Keywords: Poremećaji hranjenja; Kognitivna terapija